Common Fixed Point Results for Generalized αsp Contractive Mappings and Applications. (3rd June 2018) - Zoto, Kastriot; Vardhami, Ilir
Abstract : A class ofg - α s p -admissible mappings and general typeg - α s p contraction mappings onb -metric-like space are defined. Some fixed point results dealing with such a class of contractions are obtained. The generalized contractions considered in this work cover and unify many particular types of contractions. Finally, we present application to the existence of solutions for a system of integral equations by means ofb -metric-like spaces.